L’évolution de la philanthropie juive française à l’époque contemporaine (1791-1939) : un essai de synthèse - Laura Hobson Faure (Les Cahiers de Framespa)
This review essay traces the evolution of French Jewish philanthropy from the emancipation of the French Jewish population through the interwar period. Through an analytical reading of the historiography on this question, three distinct phenomena come to the fore: the centralization of Jewish philanthropy during the post-emancipatory period through the Consistory’s Comité de Bienfaisance Israélite de Paris, the internationalization of French Jewish philanthropy through the establishment of the Alliance Israélite Universelle, and finally its diversification, through the creation of new structures to assist Jewish immigrants from the Russian Empire, in the late 19th century. While the institutions and actors that shaped French Jewish philanthropy have been well relatively explored, this paper argues that future research should shed light on how aid was provided, especially during the interwar period. This topic is essential for our understanding of Jewish relief efforts during World War II.